Disability, Literature, Genre Representation and Affect in Contemporary Fiction - Cheyne, Ria (Liverpool University Press, 2019)
Examining the intersection of disability and genre in popular works of horror, crime, science fiction, fantasy, and romance published since the late 1960s, Disability, Literature, Genre is a major contribution to both cultural disability studies and genre fiction studies. Drawing on recent work on affect and emotion, the book explores how disability makes us feel, and how those feelings shape interpersonal and fictional encounters. Written in a clear and accessible style, Disability, Literature, Genre offers a timely reflection on the rapidly growing body of scholarship on disability representation, as well as an innovative new theorisation of genre. By reconceptualising genre reading as an affective process, Ria Cheyne establishes genre fiction as a key site of investigation for disability studies. She argues that genre fiction's unique combination of affectivity and reflexivity makes it ideally suited to the production of reflexive representations of disability: representations which encourage the reader to reflect upon what they understand about disability, and potentially to rethink it. Examining the affective-and effective-power of disability representations in a wide range of popular genre fiction, this book will be essential reading for academics in disability studies, literary studies, popular culture studies, and the medical humanities.